High-speed running and sprinting in professional adult soccer: Current thresholds definition, match demands and training strategies. A systematic review - Gualtieri, Antonio; Rampinini, Ermanno; Dello Iacono, Antonio; Beato, Marco (Frontiers in Sports and Active Living, 2023)
The aims of this systematic review were (1) to summarize the evidence on absolute velocity thresholds used to classify high-speed running and sprinting, (2) to examine the existing evidence about the individualized thresholds approach, (3) to describe high-speed and sprint running distance match demands, and (4) to provide practical applications for training high-speed and sprint running in professional adult soccer. This systematic review was conducted following the PRISMA 2020 guidelines. After the authors’ screening, 30 studies were included in this review. This review found that, to date, there is no consensus on the absolute thresholds defining high-speed and sprint running in adult soccer players. Until international standards are defined, it is reasonable to set absolute thresholds considering the range of values found in the literature collected in this review. Relative velocity thresholds could be considered for specific training sessions whose goal is to reach near maximal velocity exposure. During official matches, high-speed and sprint running distances ranged from 911 to 1063 m and 223 to 307 m, respectively, in professional female soccer players, while ranges from 618 to 1001 m and 153 to 295 m, respectively, in professional male soccer players. During training, game-based drills designed in formats using relative areas per player greater than 225 m2 and 300 m2 appear to be adequate for achieving high-speed running and sprinting exposure, respectively. The combination of game-based, running exercises and soccer circuit-based drills is advisable to ensure adequate high-speed and sprint running exposure both at a team and individual level.